ANALISIS STRATEGI KOMUNIKASI ASERTIF DALAM PENYELESAIAN KONFLIK DI LINGKUNGAN KERJA KULINER - Ramadhan, Bayu; Sarmanisa Safitriani, Nadia; Ashilah, Ajeng; Gotami, Fenny Oktavia; Maldin, Siska Amelia (JURNAL MENATA, 2025)
The culinary work environment is known for being dynamic and high-pressure, making the potential for interpersonal conflict relatively high. This study aims to examine the role of assertive and empathetic communication in resolving conflicts among workers in the culinary industry, such as in restaurant kitchens, cafés, and other food businesses. The research employs a qualitative method with a case study approach, in which data were collected through direct observation and in-depth interviews with individuals in the culinary field. The findings indicate that assertive communication characterized by the ability to express opinions firmly while still respecting others can minimize misunderstandings and enhance team collaboration. Meanwhile, empathetic communication has been shown to foster more harmonious interpersonal relationships by encouraging an understanding of others' feelings and perspectives. The conclusion of this study highlights that a combination of assertive and empathetic communication is highly effective in defusing conflict and creating a healthy and productive work atmosphere within the culinary environment.